Observations on the warm up phenomenon in angina pectoris. Issue 2 (August 1987) - Joy, M; Cairns, A W; Sprigings, D
Abstract : Adaptation to exercise was investigated in 14 men aged 34-69 years (mean 51) with stable exertional angina caused by occlusive coronary artery disease. All underwent exercise electrocardiography to symptom limitation according to the Bruce protocol (first effort), and exercise to the onset of angina (warm up) followed by four minutes' rest, followed by exercise to symptom limitation (second effort). This protocol was repeated after sequential treatment for one month each with nifedipine 10 mg three times a day and with timolol 10 mg twice a day. Warm up significantly increased walking time to the onset of angina by 34.5% and to maximal exercise by 29.5%. The heart rate and rate-pressure product were significantly higher on second effort both at the onset of angina (by 7.0% and 11.1% respectively) and at maximal exercise (by 10.5% and 15.4% respectively). ST segment displacement was not significantly different after warm up. The effect of warm up on walking time to the onset of angina was markedly reduced after treatment with nifedipine but little influenced by timolol. Mean (SE) walking time after warm up on no treatment was 10.1 (0.7) min; after treatment with nifedipine it was 10.0 (0.6) min and after treatment with timolol it was 9.7 (0.4) min. These data demonstrate a substantial improvement in exercise performance after warm up and are consistent with the hypothesis that submaximal exercise in angina pectoris facilitates myocardial oxygen uptake by coronary vasodilatation.